ICT application in teaching and learning Mandarin in Malaysia secondary schools - Chew, Fong Peng (2009)
The purpose of this study is to survey the application of ICT appliances in teaching and learning Mandarin in Malaysia secondary schools. The survey involved 31 teachers and 90 students from a few secondary schools in Malaysia. A questionnaire has been used as the survey instrument and data were processed during the SPSS program. Responses had been analyzed by using mean and standard deviation to show the teachers' and students' opinion, influencing factors, and the effects of ICT appliances applications in teaching and learning Mandarin in secondary schools in four states in Malaysia. Inferential statistics were used to analyze the data; one way ANOVA had been done to see the differences in use of ICT appliances based on social background. The results showed that both teachers and students realized the importance of CALL appliance in teaching Mandarin. Mostly, respondents agreed that ICT appliances give more positive effects in helping teachers during the process of teaching and learning Mandarin. However, many barriers constrained the teachers in teaching Mandarin by using CALL. The findings showed existence of significant difference between the frequency of using CALL appliance in teaching Mandarin with the teachers' perceptions, problems and the effectiveness of CALL appliance in teaching Mandarin.